2022
DOI: 10.23910/1.2022.2395a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Dates on the Bacterial Leaf Spot of Bottle Gourd and Pumpkin Caused by Xanthomonas cucurbitae

Abstract: An experiment was conducted at Experimental Farm, College of Horticulture and Forestry, Neri, Hamirpur during May 2019 to October, 2019 cropping season to study the effect of different sowing dates viz., 17th May (1st), 7th June (2nd), 27 June (3rd) and 17th July (4th) on the development of bacterial leaf spot of bottle gourd and pumpkin caused by Xanthomonas cucurbitae. It was observed that the mean disease severity in both bottle gourd and pumpkin crops decreased with delay in the date of sowing from mid May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…It was found that disease severity decreased with a delay in date of sowing from mid-May to the end of June (27th June) or mid-July (17th July) in pumpkin and bottle gourd [21]. A high disease severity was recorded in early sown (17 May and 7 June) crops [44]. Development of bacterial spots of bottle gourd and pumpkin was favoured by temperatures ranging between 30 and 35°C and relative humidity more than 80 per cent [21].…”
Section: Survival Disease Cycle and Epidemiologymentioning
confidence: 96%
See 3 more Smart Citations
“…It was found that disease severity decreased with a delay in date of sowing from mid-May to the end of June (27th June) or mid-July (17th July) in pumpkin and bottle gourd [21]. A high disease severity was recorded in early sown (17 May and 7 June) crops [44]. Development of bacterial spots of bottle gourd and pumpkin was favoured by temperatures ranging between 30 and 35°C and relative humidity more than 80 per cent [21].…”
Section: Survival Disease Cycle and Epidemiologymentioning
confidence: 96%
“…A similar survey was conducted in Illinois, USA, between 2010 and 2011 in pumpkin fields, which demonstrated the prevalence of bacterial spots in the field on infected fruits with 25 per cent disease incidence on an average. The survey in Jammu and Kashmir, India, including 27 areas revealed disease severity ranging from 14.5 to 33.4 per cent [24]. Bacterial leaf spot was also recorded to be a predominant disease in 60 per cent of fields of pumpkin surveyed on Caribbean Island with 30 per cent disease incidence in the rainy season [25].…”
Section: Occurrencementioning
confidence: 99%
See 2 more Smart Citations